Dysregulated Serum Lipid Metabolism Promotes the Occurrence and Development of Diabetic Retinopathy Associated With Upregulated Circulating Levels of VEGF-A, VEGF-D, and PlGF - Zhang, Xinyuan; Qiu, Bingjie; Wang, Qiyun; Sivaprasad, Sobha; Wang, Yanhong; Zhao, Lin; Xie, Rui; Li, Lei; Kang, Wenting (Frontiers in Medicine, 2021)
Purpose: This study aims to explore the correlations of arteriosclerosis-associated plasma indices with various severity levels of DR and to test the hypothesis that elevated circulating level of known angiogenic cytokines induced by hyperglycemia is associated with dyslipidemia on DR. Methods: This cross-sectional study consists of 131patients with type 2 diabetes. The patients were categorized based on their diabetic retinopathy (DR) status into those with no DR (DM), non-proliferative diabetic retinopathy (NPDR), and proliferative diabetic retinopathy (PDR) groups. The biochemical profile including fasting glucose, HbA1c, lipid profile were estimated, plasma angiogenic cytokines [VEGF-A, C, D and placental growth factor (PlGF) were analysed by protein microarrays. The atherogenic plasma index (API) was defined as LDL-C/HDL-C; atherogenic index (AI) was calculated as (TC-(HDL-C))/ HDL-C and atherogenic index of plasma (AIP) was defined as log (TG/HDL-C). Results: No significant differences were detected in the duration of hypertension, age, and gender between the three groups. Serum TC and LDL-C, AI and API in the NPDR group and PDR group were significantly higher than those in the DM group. The circulating level of PlGF, VEGF-A and VEGF-C were significantly correlated with the severity of DR. VEGF D-is a risk factor independent of API (Z=-2.61, P=0.009) and AI (Z=-2.40, P=0.016). Multivariate logistic regression showed that AI and API are strong risk factors for the occurrence and severity of DR. Associated with AI and API, VEGF-D and PlGF contribute to DR: VEGF-D [AI: P=0.038, odd ratio (OR)=1.38; VEGF-D: P=0.002, OR=1.00. API: P= 0.027, OR=1.56, VEGF-D:P=0.002, OR=1.00] and PlGF [AI: P=0.021, OR=1.43; VEGF-D: P=0.004, OR=1.50. API: P= 0.011, OR=1.66; VEGF-D:P=0.005, OR=1.49]. Conclusions: TC and LDL-C are risk factors for presence of any DR. AI and API are novel and better predictive indicators for the occurrence and severity of DR in comparion with the traditional lipid profiles. Abnormal lipid metabolism are associated with the upregulation of circulating cytokines that are linked to the severity of DR.